2020
DOI: 10.33963/kp.15591
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in patients with chronic coronary syndromes over a 20-year period (1997–2017)

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There is strong scientific evidence that the long-term survival of coronary patients may be improved by providing optimal cardiovascular prevention [8]. The increasing proportion of obese patients may be responsible for the increase in hypertension, dyslipidemia, and diabetes prevalence as well as for insufficient improvement in the control of these risk factors despite increase in the drugs prescription rates in patients with coronary artery disease [4,13,22]. The present results urge to improve cardiovascular prevention in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 75%
“…There is strong scientific evidence that the long-term survival of coronary patients may be improved by providing optimal cardiovascular prevention [8]. The increasing proportion of obese patients may be responsible for the increase in hypertension, dyslipidemia, and diabetes prevalence as well as for insufficient improvement in the control of these risk factors despite increase in the drugs prescription rates in patients with coronary artery disease [4,13,22]. The present results urge to improve cardiovascular prevention in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 75%
“…Several previous studies have also shown that myocardial revascularization is not only more effective in reducing angina and the need for antianginal drugs, but also improves physical performance and quality of life compared to the conservative treatment strategy both in a short-and long-term follow-up [17,18]. However, the failure to properly implement lifestyle changes may contradict the benefits arising from the rapid development of pharmacological and invasive treatment of coronary artery disease observed in recent years [8,19,20]. The present analysis shows no significant improvement in the control of the main CAD risk factors and no significant change in the proportion of patients reporting the use of antiplatelets, β-blockers, and lipid-lowering drugs 6-18 months after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Although the morbidity and case-fatality in acute myocardial infarction survivors has decreased over recent decades, mainly thanks to spread of pharmacological and invasive treatment methods, the decrease in cardiovascular risk is lower than one could expect based on the results of randomized trials of new therapies. This confusion could be partly explained on the basis of our results showing a gradual increase in central obesity prevalence which probably counteract the favorable changes in the management of CAD [ 10 ].…”
mentioning
confidence: 99%